Results of metallographic observations of cultivator shares after spot electromechanical processing. Issue 1 (1st February 2022) - Yakovlev, Sergey; Kurdyumov, Vladimir; Ayugin, Nikolay; Mishanin, Alexandr
Abstract: Presented are the results of metallographic studies of the structure and properties of a cultivator share, hardened by spot electromechanical processing in its various high-wear areas. In the process of research, the manufacturer was offered recommendations on the technology of forming parts in the process of their manufacture. It has been established that spot electromechanical processing allows to obtain hemispherical hardened areas with a hardness of HV 7000 ... 7600 MPa, which will provide the effect of self-sharpening of their cutting parts during the operation of the cultivator shares. Spot electromechanical processing with two tools allows to provide through hardening of the cultivator share along the ends of the share wings. The proposed technology for hardening cultivator shares during their manufacture and repair will increase the durability of these parts during their operation.